(untitled) (Global Journal of Human-Social Science, 2013)
Training plays its crucial part in every field In this research work the role of training is evaluated in education sectors in Pakistan through primary data The data was collected from trained and untrained teachers The performance parameters are determined and then the performance of teachers is evaluated on these predetermined parameters It was concluded that there is a significant difference between the performance of trained and untrained teachers in specific performance areas